2012
DOI: 10.1007/jhep09(2012)067
|View full text |Cite
|
Sign up to set email alerts
|

No existence of black holes at LHC due to minimal length in quantum gravity

Abstract: We investigate the impact of the Generalized Uncertainty Principle (GUP), proposed by some approaches to quantum gravity such as String Theory and Doubly Special Relativity Theories (DSR) on the production of mini black holes, and show that the minimum black hole mass is formed at energies higher than the energy scales of LHC which possibly agrees with the recent experimental results of LHC [1,2]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Motivated again, by black hole physics, there is an another interesting connection between the Hawking radiation and the uncertainty principle [7][8][9][10][11][12][13] where the black hole can be modeled as n-dimensional sphere of size equal to twice of Schwarzschild radius. Since the Hawking radiation is a quantum process, one could assume that the emitted particles should obey the Heisenberg uncertainty relation.…”
Section: Jhep06(2014)093mentioning
confidence: 99%
See 4 more Smart Citations
“…Motivated again, by black hole physics, there is an another interesting connection between the Hawking radiation and the uncertainty principle [7][8][9][10][11][12][13] where the black hole can be modeled as n-dimensional sphere of size equal to twice of Schwarzschild radius. Since the Hawking radiation is a quantum process, one could assume that the emitted particles should obey the Heisenberg uncertainty relation.…”
Section: Jhep06(2014)093mentioning
confidence: 99%
“…By employing this GUP, it was found that the black hole thermodynamics quantities, such as temperature, and entropy are completely modified such that the end-point of Hawking radiation is not catastrophic anymore. This is because the GUP implies the existence of black hole remnants at which the specific heat vanishes and, therefore, the black hole cannot exchange heat with the surrounding space [7][8][9][10][11][12][13]. This means that GUP prevents the black hole from evaporating completely, just like the standard uncertainty principle prevents the hydrogen atom from collapsing.…”
Section: Jhep06(2014)093mentioning
confidence: 99%
See 3 more Smart Citations